2016
DOI: 10.1128/aem.03457-15
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Distribution of Cysts from the Toxic Dinoflagellate Cochlodinium polykrikoides in Bloom-Prone Estuaries by a Novel Fluorescence In Situ Hybridization Assay

Abstract: Cochlodinium polykrikoides is a cosmopolitan dinoflagellate that is notorious for causing fish-killing harmful algal blooms (HABs) across North America and Asia. While recent laboratory and ecosystem studies have definitively demonstrated that Cochlodinium forms resting cysts that may play a key role in the dynamics of its HABs, uncertainties regarding cyst morphology and detection have prohibited even a rudimentary understanding of the distribution of C. polykrikoides cysts in coastal ecosystems. Here, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 61 publications
(106 reference statements)
0
12
0
Order By: Relevance
“…According to the hypothesis of Hattenrath-Lehmann et al . 28 , vegetative cells of C. polykrikoides were present during 2015, as evident from observation of the sediments in Tongyeong area in 2014. However, vegetative cells of C. polykrikoides were not detected during the summers of 2015 and 2017 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…According to the hypothesis of Hattenrath-Lehmann et al . 28 , vegetative cells of C. polykrikoides were present during 2015, as evident from observation of the sediments in Tongyeong area in 2014. However, vegetative cells of C. polykrikoides were not detected during the summers of 2015 and 2017 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Hattenrath-Lehmann et al . 28 reported that low cyst densities after high-density blooms may be affected by several physical, chemical, and biological factors, which suggest that a small portion of the vegetative population is involved in sexual reproduction 22 . Moreover, the other factors affecting density of cysts include grazing of cysts in sediments 29 , bacterial degradation of cysts 8 , and/or the dispersal of cysts/vegetative cells out of the bloom region via currents 30 , followed by deposition of these cysts elsewhere 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the occasional non‐specific fluorescence in non‐target cells or particles (e.g., pollen grains) in FISH samples as reported in previous work (Hattenrath‐Lehmann et al. ), the fluorescing cells observed in the samples that were subject to FISH using both Cy3‐ and FITC‐labeled probes were carefully observed under bright field microscopy for the cyst morphology (i.e. to compare with that observed in laboratory cultures) and were then selectively micropipetted for single‐cell PCR and sequencing (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Real-time PCR amplification to quantify DNA genes from sediments has been shown to be a good proxy for cyst abundances, including some Alexandrium species (Kamikawa et al, 2007, Erdner et al, 2010, Park and Park, 2010. Lastly, cyst species have been mapped using the fluorescence in situ hybridization (FISH) technique (Hattenrath-Lehmann et al, 2016). Genetic techniques can therefore be used to provide reliable information on accumulation spots of cysts and to infer ecological patterns.…”
Section: Introductionmentioning
confidence: 99%